Islam and Citizenship in Indonesia: Democracy and the Quest for an Inclusive Public Ethics - Taufiq, Firmanda (Islamic Studies Review, 2024)
Islam and Citizenship in Indonesia: Democracy and the Quest for an Inclusive Public Ethics (Robert W. Hefner) London and New York: Routledge, 2024 https://doi.org/10.56529/isr.v2i2.211